Individual Differences Facing the COVID-19 Pandemic: The Role of Age, Gender, Personality, and Positive Psychology - Bernabe-Valero, Gloria; Melero-Fuentes, David; De Lima Argimon, Irani I.; Gerbino, Maria (Frontiers in Psychology, 2021)
Research on individual differences in facing the COVID-19 seems to be crucial in order to design differential intervention strategies that optimize the effectiveness of these interventions. In this research, a sample of 302 North American participants were recruited through the crowdsourcing platform ProA and different profiles were established, profiling variables of interest in order to face COVID-19 outbreak. Socio-demographic and psychological (personality traits, gratitude, meaning of life and religiosity) variables were explored. These results are of interest to depeen on the study of individual differences in a theoretical and applied level.